An innovative simulation model for the operations of a multipurpose seaport: a case study from Port of Wilmington, USA. (2017) - Wahed, Mir A.; Faghri, Ardeshir; Li, Mingxin
The analysis of potential operating problems in a port facility is an enduring theoretical and practical problem. Because of the complexity of the problem, many existing methods have difficulties in providing a fast and reliable analysis of potential operating problems in a multipurpose port facility. In this study, a simulation model is developed to overcome this difficulty by analysing the operation of a multipurpose regional seaport in Delaware, USA. The model is implemented to identify the possible bottlenecks and optimise the operation of the port. The results of the simulation model are used to choose the optimal change in the significant elements (ship turnaround time, waiting time for bulk cargoes, containers, and trucks) of the terminal's operation.